PERAN EDUKASI IBU DALAM RUMAH TANGGA - Siame, Norma Dg. (Institut Agama Islam Negeri (IAIN) Palu, 2005)
Mother plays a key role at home, especially in nurturing her children. It goes without saying that early education accepted by a child comes from a mother. She has great contribution to build character of young generation. That is why Qurâanic verses and the Prophet Tradition (hadith) indicate how,Â without mincing words that,Â mother should treat her children, even early before they are born.Â Â Â Â Â Â Â Â Â Â Â This article tries to analyze educative role of mother at home by exploring Qurâanic verses and hadith as well as by quoting expert views. In addition, it suggests outdoor factors influencing children education.Â Kata Kunci: Pendidikan, Ibu, Rumah tangga